2016
DOI: 10.1002/smll.201600191
|View full text |Cite
|
Sign up to set email alerts
|

Layered MoS2 Hollow Spheres for Highly‐Efficient Photothermal Therapy of Rabbit Liver Orthotopic Transplantation Tumors

Abstract: Combining photothermal therapy (PTT) with clinical technology to kill cancer via overcoming the low tumor targeting and poor therapy efficiency has great potential in basic and clinical researches. A brand-new MoS2 nanostructure is designed and fabricated, i.e., layered MoS2 hollow spheres (LMHSs) with strong absorption in near-infrared region (NIR) and high photothermal conversion efficiency via a simple and fast chemical aerosol flow method. Owing to curving layered hollow spherical structure, the as-prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 39 publications
0
59
0
Order By: Relevance
“…Safe, stable, and highly efficient materials in nanomedicine have gained momentum in the treatment of various types of malignancies, including HCC. Aiming at the characteristic microenvironment of HCC, nanocarriers with excellent stability and targetability have been constructed, and their combinations with new therapeutic modalities such as sonodynamic, photodynamic, and photothermal therapy (PTT) have shown great potential in the treatment of HCC. PTT has been widely recognized with its minimal damage to normal tissues and high ablation efficacy, which is typically triggered by photothermal‐transducing agents (PTAs) under near infrared (NIR) laser to in situ generate heat for the thermal ablation of cancer cells .…”
Section: Methodsmentioning
confidence: 99%
“…Safe, stable, and highly efficient materials in nanomedicine have gained momentum in the treatment of various types of malignancies, including HCC. Aiming at the characteristic microenvironment of HCC, nanocarriers with excellent stability and targetability have been constructed, and their combinations with new therapeutic modalities such as sonodynamic, photodynamic, and photothermal therapy (PTT) have shown great potential in the treatment of HCC. PTT has been widely recognized with its minimal damage to normal tissues and high ablation efficacy, which is typically triggered by photothermal‐transducing agents (PTAs) under near infrared (NIR) laser to in situ generate heat for the thermal ablation of cancer cells .…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of PDT involves energy transfer from the light‐excited PSs to oxygen and other molecules in the tissue to generate ROS, particularly singlet oxygen, which induces cellular toxicity . However, PTT usually relies on the photothermal agents that can transform strong absorbed light energy to heat, causing thermal ablation to target cells . Therefore, a higher therapy effect by combination of these two phototherapy methods under single light irradiation can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…From the TEM image in Figure a, it was observed that the as‐prepared MoS 2 nanosheets were well dispersed with an average size of approximately 150 nm. The SAED (selected area electron diffraction) pattern in the inset of Figure a further confirmed that the obtained MoS 2 nanosheets owned hexagonal structure with (100), (110), (103), and (002) planes . The HRTEM (Figure b) image clearly showed well resolved lattice planes with average spacing of 0.27 and 0.65 nm, which corresponded to the (100) and (002) lattice spacing of the MoS 2 nanosheets, respectively.…”
Section: Resultsmentioning
confidence: 87%